Pengembangan Sistem Pelaporan Data Hasil Inspeksi Barang Berbasis Web - Siska Putriani (STMIK Dian Cipta Cendikia Kotabumi, 2021)
The purpose of this study is to describe the application and manage data of the system of reporting for goods in PT. Amindoway Jaya web-based. With descriptive qualitative methods, it allows product results that have a high level of checking and reduce errors. Then check the products from beginning to end and have their own SOP for products that are defective or damaged and cannot be used anymore. The results of a good analysis show that the company has undergone good quality control well, but the quality control reporting process and the search for defect reports take a long time because they have to recap one by one the less systematic checking forms. To overcome this problem, it is necessary to develop an information system for quality control and defect reports. Descriptive qualitative method to analize data and Unified Modelling Language (UML) to analize the design of the system to be developed. With the system design that will be developed, it is hoped that it can overcome the problems faced by PT Amindoway Jaya related to monitoring quality control reports and defective products